Phosphonate analogues of dinucleotides as substrates for DNA-dependent RNA polymerase from Escherichia coli in primed abortive initiation reaction - Cvekl, A; Horská, K; Sebesta, K; Rosenberg, I; Holý, A (International journal of biological macromolecules, 1989)
Dinucleotides (3'-5')-ApU and UpA and their 3'-O-phosphonylmethyl and 5'-O-phosphonylmethyl analogues were studied as substrates in the primed abortive synthesis catalysed by Escherichia coli DNA-dependent RNA polymerase on poly[d(A-T)] template. All phosphonate analogues of dinucleotides containing the anomalous sugar-phosphate backbone are substrates for the holoenzyme as verified by RNase A and RNase T2 digestion of the trinucleotide analogues obtained. The finding that phosphonate dinucleotides act as primers for transcription indicates that steric requirements at the initiation site are not as specific as previously supposed. Analysis of kinetic constants of ordered bibi reaction Kia, KmA, KmB and Vmax suggests that the instability of short RNA-DNA hybrids contributes to the abortive release of trinucleotides formed.
Keywords: genetická transkripce; organofosfonáty; Electrophoresis, Polyacrylamide Gel; Transcription, Genetic; Poly dA-dT; poly dA-dT; Dinucleoside Phosphates; Kinetics; Organophosphonates; Escherichia coli; elektroforéza v polyakrylamidovém gelu; Substrate Specificity; DNA-Directed RNA Polymerases; substrátová specifita; kinetika; DNA řízené RNA-polymerasy; dinukleosidfosfáty